The genetic diversity of ayam ketawa (Gallus gallus domesticus, Linneaus, 1758) in Bangkalan District, Madura Island, Indonesia - ABINAWANTO Abinawanto; TRI ZULISTIANA; RETNO LESTARI; ASTARI DWIRANTI; ANOM BOWOLAKSONO (Society for Indonesian Biodiversity, 2021)
Abstract. Abinawanto, Zulistiana T, Lestari R, Dwiranti A, Bowolaksono A. 2021. The genetic diversity of ayam ketawa (Gallus gallus domesticus, Linneaus, 1758) in Bangkalan District, Madura Island, Indonesia. Biodiversitas 22: 3145-3155. Ayam Ketawa, a variation of Gallus gallus domesticus Gallus gallus domesticus, comes from Sidendreng-Rappang (Sidrap) District, South Sulawesi, Indonesia. Apart from Sidrap, ayam ketawa farms are also found in Bangkalan District, on the island of Madura, Indonesia. Ayam ketawa from Bangkalan District often wins national level contests. Therefore, the research was carried out with the aim of knowing the genetic diversity of ayam ketawa in Kamal Subdistrict, Socah Subdistrict, and Burneh Subdistrict, based on bioacoustic, morphometric, and barcoding DNA analysis. The studied ayam ketawa consists of dangdut and slow types. The longest duration (6.00 ± 3.0) seconds was shown by ayam ketawa from Kamal Subdistrict, while the highest number of syllables (7.20 ± 5.80) came from Socah Subdistrict. The results of the Mann-Whitney test showed that eight morphological characters were significantly different (P <0.05) between ayam ketawa population in Kamal and Burneh subdistricts, namely body weight, femur length, shank length, shank circumference, wing length, comb height, third finger length, and breastbone length. Four morphological characters differed significantly (P <0.05) between ayam ketawa population in Kamal and Socah subdistricts, namely shank length, wing length, third finger length, and sternum length. Three morphological characters were significantly different (P <0.05) between the Burneh and Socah subdistricts population, namely body weight, femur length, and shank circumference. The analysis results of DNA Barcoding gene of the Cytochrome Oxidase subunit 1 (CO1) showed a genetic distance ranging from 0.025 to 1.872.